Impact of testosterone treatment on circulating irisin in men with late-onset hypogonadism and metabolic syndrome. (4th December 2020) - Assyov, Yavor; Gateva, Antoaneta; Karamfilova, Vera; Gatev, Tsvetan; Nedeva, Iveta; Velikova, Tsvetelina; Kamenov, Zdravko Asenov
Abstract: Objectives: The beneficial effects of testosterone replacement therapy (TRT) in men with late-onset hypogonadism (LOH) on the body composition and metabolic outcomes are well-established. A potential explanation might lie in the hormones, secreted from skeletal muscles, named "myokines". The aim of this study was to evaluate the effects of TRT on the levels of serum irisin in subjects with LOH. Study Design: A total 40 men with metabolic syndrome (MS) and LOH (measured serum testosterone concentration < 12 nmol/l). TRT with Testosterone Undecanoate (Nebido™) was performed at baseline and at week 6. Irisin serum concentration was determined at baseline and at week 18 by means of ELISA. Results: Circulating irisin was positively associated with serum testosterone (r = 0.283, p < 0.05). TRT has led to a statistically significant rise in circulating serum irisin levels (7.12 ± 0.76 mcg/ml versus 7.76 ± 0.75 mcg/ml; paired-samples t-test p < 0.001). ROC-analyses determined irisin to be predictive of treatment response (AUC = 0.741, p = 0.014). Conclusions: Irisin is positively associated with serum testosterone in a population of men with MS and LOH. TRT in these subjects has led to a significant improvement in associated clinical symptoms as well as to a significant rise in serum irisin levels.